2012
DOI: 10.1007/s00436-011-2791-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and immunolocalization of a protein disulfide isomerase from Angiostrongylus cantonensis

Abstract: Protein disulfide isomerases (PDIs), belonging to the thioredoxin superfamily, are oxidoreductases that catalyze the formation, reduction, and isomerization of disulfide bonds among cysteine residues of proteins. In this study, we report the cloning and characterization of a cDNA encoding a protein disulfide isomerase (AcPDI) from a cDNA library of fourth-stage larvae of Angiostrongylus cantonensis. The deduced amino acid sequence contains two thioredoxin domains and exhibits high identity to the homologues fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The reduction of cCMP by active RNase into CMP was monitored by the absorbance at 296 nm for 60 min in a Microplate Reader (Thermo, Varioskan Flash). For the PDI reductive assay, the MgPDI enzyme activity to reduce insulin was determined by a modified method 41,42 . Reaction mixtures (200 μl) included 100 mM Tris-Cl (pH 6.8), 2 mM ethylenediaminetetraacetic acid (EDTA), 0.13 mM insulin from bovine pancreas (Sigma), 0.33 mM dithiothreitol (DTT) and increasing concentrations (ranging from 2.5 to 10 μM) of purified MgPDI protein.…”
Section: Methodsmentioning
confidence: 99%
“…The reduction of cCMP by active RNase into CMP was monitored by the absorbance at 296 nm for 60 min in a Microplate Reader (Thermo, Varioskan Flash). For the PDI reductive assay, the MgPDI enzyme activity to reduce insulin was determined by a modified method 41,42 . Reaction mixtures (200 μl) included 100 mM Tris-Cl (pH 6.8), 2 mM ethylenediaminetetraacetic acid (EDTA), 0.13 mM insulin from bovine pancreas (Sigma), 0.33 mM dithiothreitol (DTT) and increasing concentrations (ranging from 2.5 to 10 μM) of purified MgPDI protein.…”
Section: Methodsmentioning
confidence: 99%
“…Proper folding of proteins is necessary for parasite reproduction, development and play a pivotal role in host parasite interactions. Recently it was shown that PDI is vigorously expressed in the uterus wall and oocyte of female adult A. cantonensis worms (Liu et al, 2012[ 28 ]). The formation and maturation of proteins occur throughout the whole life and vitellogenins are prevalent proteins in adult female nematodes that are synthesized in a large amount to support developing oocytes (Nisbet et al, 2010[ 37 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The transcripts found in pepsin-activated infective larvae (3rd-stage) encode proteins that participate in a wide range of biological processes (Chang et al 2011). Although cloning of galectin (Hao et al 2007), cystatin (Liu et al 2010), Ac16 (Li et al 2011), cathepsin B (Han et al 2011), a cathepsin B-like cysteine proteinase (Cheng et al 2012) and a protein disulphide isomerase (Liu et al 2012) has been accomplished in A . cantonensis , the characterisation of these proteins is far from complete.…”
mentioning
confidence: 99%